Implementasi Sorogan dalam Pembelajaran Qirā’ah Kitab Kuning di Pesantren al-Luqmaniyyah Yogyakarta - Maslahul Adi, Habib Maulana; Zidni, A. M. Irfan; Maslahul Adi, Nur Romdlon; Rilitama, Angga (STAINI Press, 2024)
This research aims to reveal and describe the implementation of sorogan in learning qirā'ah kitab kuning at the Pesantren Al-Luqmaniyyah Yogyakarta. This research uses a qualitative approach, with a case study type. There are primary and secondary data sources, which are collected through observation, interviews, and documentation. The validity of the data was tested using method triangulation techniques and source triangulation. Data analysis was carried out using inductive techniques and presented using descriptive techniques. The findings from this research are that the implementation of sorogan at the Pesantren Al-Luqmaniyyah Yogyakarta is only mandatory for students at the beginning and middle levels, in groups of 3-5 people per supervisor, and the reading provided is adjusted to the class. Supporting factors for the implementation of sorogan are the suitability of sorogan with traditional pesantren, the synergy of pesantren administrators with the education board, the sufficient number and skills of supervisors, the uniform knowledge of students, and the accessibility of learning support references. Meanwhile, the inhibiting factors are the lack of consistency of supervisors, less than optimal preparation of students, unstable motivation to learn, and the many activities outside the pesantren that students also have to participate in. It is hoped that the results of this research can be used as evaluation material for the management of the Pesantren Al-Luqmaniyyah Yogyakakarta, as well as consideration for other pesantren that are or will be implementing the sorogan method in their learning systems.